COMPANY SIZE MODERATES CAPITAL INTENSITY, SALES GROWTH, AND MANAGERIAL OWNERSHIP ON TAX AVOIDANCE - Anggraini, Anggun; Indawati, Indawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to examine the effect of capital intensity, sales growth and managerial ownership on tax avoidance. This research was conducted on mining companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. Hypothesis testing was carried out using the Eviews 9 application. The samples used in this study were 42 samples of mining companies. sampling method using purposive sampling by using several criteria in accordance with research needs. The analysis technique used in this research is panel data regression. The data studied were obtained from the Indonesian Capital Market Directory (ICMD) of each company. The results of this study simultaneously capital intensity, sales growth and managerial ownership affect tax avoidance. Partially, capital intensity and managerial ownership have no effect on tax avoidance, while sales growth has an effect on tax avoidance. The test results using moderation show that company size can strengthen capital intensity, company size can weaken sales growth. firm size can strengthen managerial ownership.